HUBUNGAN ANTARA JOB INSECURITY DENGAN KESEJAHTERAAN PSIKOLOGIS PADA KARYAWAN KONTRAK DI KOTA MEDAN - Sicha Ladiska Tambunan; Karina M Brahmana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Contract-based employment is frequently associated with uncertainty regarding job continuity; however, its psychological consequences do not necessarily manifest in the same way across workers. This study examined the relationship between job insecurity and psychological well-being among contract employees in Medan City using a quantitative correlational design. A total of 166 respondents were recruited through non-probability sampling with a purposive sampling approach. Data were collected using a job insecurity scale adapted from Greenhalgh and Rosenblatt and Ashford et al. (1989), while psychological well-being was measured using an instrument developed based on Ryff’s (1989) multidimensional model. The relationship between the two variables was analyzed using Spearman’s rho correlation. The findings revealed no significant relationship between job insecurity and psychological well-being (r = 0.016; p = 0.834). Most respondents reported a moderate level of job insecurity, whereas their psychological well-being was generally categorized as high. These findings suggest that the psychological well-being of contract employees is not determined solely by perceptions of job security but is also shaped by adaptive capacity, coping strategies, and the availability of social support. This study contributes to the field of occupational psychology by demonstrating that psychological well-being is a multidimensional construct that is sustained through the combined influence of personal resources and organizational support. ABSTRAK Status kerja kontrak sering dikaitkan dengan ketidakpastian mengenai keberlanjutan pekerjaan, namun konsekuensi psikologis dari kondisi tersebut tidak selalu berkembang secara seragam pada setiap pekerja. Penelitian ini mengeksplorasi keterkaitan antara job insecurity dan psychological well-being pada karyawan kontrak di Kota Medan melalui pendekatan kuantitatif dengan rancangan korelasional. Sebanyak 166 responden direkrut menggunakan teknik non-probability sampling melalui purposive sampling. Pengumpulan data memanfaatkan skala job insecurity yang diadaptasi dari Greenhalgh dan Rosenblatt serta Ashford et al. (1989), sementara psychological well-being diukur menggunakan instrumen yang mengacu pada dimensi Ryff (1989). Hubungan antarvariabel dianalisis menggunakan korelasi Spearman's rho. Analisis menunjukkan bahwa job insecurity tidak berhubungan secara signifikan dengan psychological well-being (r = 0,016; p = 0,834). Responden umumnya memperlihatkan tingkat job insecurity pada kategori sedang, sedangkan psychological well-being berada pada kategori tinggi. Temuan ini mengindikasikan bahwa kesejahteraan psikologis pekerja kontrak tidak semata-mata ditentukan oleh persepsi terhadap keamanan kerja, tetapi juga dipengaruhi oleh kemampuan beradaptasi, strategi coping, serta dukungan sosial yang tersedia. Dengan demikian, penelitian ini memperkaya kajian psikologi kerja dengan menegaskan bahwa psychological well-being merupakan konstruk yang multidimensional sehingga penguatannya memerlukan sinergi antara sumb er daya personal dan dukungan organisasi.